Debridement arthroplasty of a rare case of elbow stiffness. A case report and literature review. (2018) - Poonit, Keshav; Yao, Chenglun; Zhou, Xijie; Wu, Zhipeng; Lin, Damu; Yan, Hede
Highlights: Melorheostosis of the elbow associated with elbow stiffness is extremely rare. In the standard radiology or orthopedics literature Melorheostosis (from the Greek: melos = limb, rheos = flow) is described monotonously as a "flowing hyperostosis" resembling dripping candle wax. Patients with this condition may have joint pain, stiffness, deformity, and restricted range of motion due to bony and soft-tissue contracture. Involvement usually follows a sclerotomal distribution and usually affects only one extremity. There is no standard treatment for melorheostosis, and management plans must be made on an individual patient basis. The aims of treatment are pain relief and maintaining function. Some Surgical treatment for this condition includes tendon lengthening, excision of fibrous and osseous tissue, fasciotomy, capsulotomy, sympathectomy, corrective osteotomy, Ilizarov lengthening, arthrodesis, implant arthroplasty, and even amputation of severely affected limbs with vascular ischemia. In this study we found that debridement arthroplasty is safe and effective in treating elbow stiffness associated with Melorheostosis. Abstract: Introduction: Elbow stiffness is a common condition that affects the quality of life of patients. Melorheostosis of the elbow associated with elbow stiffness is extremely rare. Presentation of case: We report the case of a 28 yr old male who presented with elbow stiffness which occurred within one year without prior history of trauma or infection. The patient had decrease in range of motion together with progressive worsening pain that forced him to seek medical attention. Discussion: There is no standard treatment for melorheostosis, and management plans must be made on an individual patient basis. The aims of treatment are pain relief and maintaining function. Conclusion: Debridement arthroplasty is safe and effective in treating elbow stiffness associated with Melorheostosis.